Patient perceptions concerning pain management in the treatment of rheumatoid arthritis. - Taylor, P; Manger, B; Alvaro-Gracia, J; Johnstone, R; Gomez-Reino, J; Eberhardt, E; Wolfe, F; Schwartzman, S; Furfaro, N; Kavanaugh, A (2010)
Previous qualitative studies have revealed discrepancies between patients' and physicians' perceptions of rheumatoid arthritis (RA) and its treatment. Questionnaires were administered to 2795 patients with RA (756 from Europe; 2039 from the USA) to measure patients' perceptions regarding pain management in RA. Although the majority of patients reported their RA as somewhat-to-completely controlled, 75% of European and 82% of US patients reported their pain as moderate-to-severe in the previous 2 months. The majority of European (60%) and US (65%) patients reported dissatisfaction with their arthritis pain. Patients' pain levels corresponded with their disease severity. A higher percentage of patients who reported severe pain were being treated for depression than those who had moderate or mild pain. Patients in the USA rated pain relief as the top required benefit from their RA medication. A comprehensive examination of patients' perspectives regarding pain could lead to better patient care and pain management strategies.